A Pilot Study to Assess Hydration in Geriatric Patients by Bioimpedance - Hlubik, Jan; Vyslouzilova, Lenka; Studnicka, Filip; Vychodil, Rostislav; Lhotska, Lenka (Studies in health technology and informatics, 2023)
Hydration plays a very important role in old age. This is because hydration changes over the course of life and therefore geriatric patients need to have their hydration monitored. However, the general problem is that there are no completely reliable methods' that can measure this. In this paper we performed a pilot monitoring in geriatric patients and compared directly measured electrical data with results from biochemistry. The observed correlations on our pilot sample show very promising values for (r=0.68) creatinine correlation with phase angle and (r=0.71) creatinine correlation with NI (nutritional index). It also shows that electrical readings may in the future indicate much more accurately the true status of the patient. Our research is still ongoing, and we are planning further measurements on a larger sample.
Keywords: hodnocení stavu výživy; Aged; Creatinine; lidé; Electric Impedance; Humans; Pilot Projects; elektrická impedance; pilotní projekty; Longitudinal Studies; longitudinální studie; senioři; Nutrition Assessment; kreatinin